Xanthine oxidase inhibitory kinetics and mechanism of ellagic acid: In vitro, in silico and in vivo studies - Jianmin Chen; Zemin He; Sijin Yu; Xiaozhen Cai; Danhong Zhu; Yanhua Lin (IET Nanobiotechnology)
Abstract Ellagic acid (EA), which is widely distributed in many foods, has been found to possess inhibitory activity against xanthine oxidase (XO). However, there is ongoing debate about the difference in XO inhibitory activity between EA and allopurinol. Additionally, the inhibitory kinetics and mechanism of EA on XO are still unclear. Herein, the authors systematically studied the inhibitory effects of EA on XO. The authors’ findings showed that EA is a reversible inhibitor with mixed‐type inhibition, and its inhibitory activity is weaker than allopurinol. Fluorescence quenching experiments suggested that the generation of EA‐XO complex was exothermic and spontaneous. In silico analysis further confirmed that EA entered the XO catalytic centre. Furthermore, the authors verified the anti‐hyperuricemia effect of EA in vivo. This study elucidates the inhibition kinetics and mechanism of EA on XO, and lays a theoretical foundation for the further development of drugs and functional foods containing EA for the treatment of hyperuricemia.